Comparative study to determine self-medication practice and pattern in urban and rural areas of Etawah district - Singh, Nishant; Singh, Naresh Pal; Jain, Pankaj Kumar; Singh, Vaibhav; Chaurasiya, Shailendra; Verma, Ravikant; Ranjan, Mridula (International Journal Of Community Medicine And Public Health, 2019)
Background: According to William Osler, a great feature which distinguishes man from animals is the desire to take medicine. Self-medication is an age old practice. According to World Health Organization guidelines “self-medication is defined as use of medicinal products by the individuals to treat self-recognized disorders or symptoms, or the intermittent or continuous use of a medication prescribed by a physician for chronic or recurring diseases or symptoms. Methods: It was a cross sectional study, which was conducted among residents of urban and rural areas of Etawah district, Uttar Pradesh by using 40×5 cluster sampling. The data was collected by using pre designed, semi-structured questionnaire. Proforma included socio- demographic profile, practice of self- medication and pattern of self-medication. Results: Most of the participants who indulged in self-medication in urban areas 69.5% and rural areas 65% belong to the age group 20-39 years. Majority of the participants (51.0%) in urban areas belonged to the nuclear family while most of the participants (50%) belonged to joint family followed by nuclear family (40%) in rural areas. most common reason for self-medication in urban area was the availability of old prescription which is present in 30.0% (60) of subjects but in rural area most common reason for self-medication was high fee of doctor which was 29.0% (58). Conclusions: Most common age group indulged in self-medication was 20-39 years. Most common reason for self-medication was availability of old prescription at home while in rural area, high fees of doctor was the common reason for self-medication.